(untitled) (Texas Journal of Multidisciplinary Studies, 2022)
This article deals with the issues related to the use of flight simulator in aviation. It also discusses the scope of simulator using in flight training processes for particular aviation ratings. Furthermore, advantages and disadvantages of using flight simulators are given. In addition, the methods for using flight simulation devices in pilot training and practical training processes are presented, taking into consideration military aviation features.